Analisis Pengaruh Emisi Zat Karbon terhadap Kerusakan Kualitas Udara dan Pencemaran Lingkungan - Fairuz Rofifah Arifin; Nazwa Aulia Rahman (Journal Innovation In Education, 2024)
Carbon monoxide is called the "silent killer" because this gas is colorless and odorless. This gas is produced from incomplete combustion of fossil fuels. Carbon monoxide, referred to as CO, is flammable and very dangerous but is non-irritating and tasteless, making it difficult to detect by the human senses. Carbon monoxide can form naturally or artificially. Human activities are the main source of its formation. Carbon monoxide (CO) which comes from nature is CO gas which comes from oceans, mountains, forest fires, electrical storms and metal oxidation in the atmosphere. The source of CO gas that comes from human activities generally comes from incomplete combustion processes, such as the combustion process that occurs in motorized vehicles, burning coal, combustion products from industrial machines, cigarette smoke or other combustion that produces gas. This research aims to determine the effect of carbon monoxide on the environment and health. The method used in this writing is literature study. The library sources taken in compiling this literature study were through journals taken from the Google Scholar website. The results are based on a review of (number of journals) journals related to the title, namely the effect of carbon emissions on damage to air quality and environmental pollution.